2009
DOI: 10.1203/pdr.0b013e31819da21b
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Functional Residual Capacity at Birth: The Effect of Sustained Inflation and Positive End-Expiratory Pressure in a Preterm Rabbit Model

Abstract: The effect of a 20 s sustained inflation (SI) and positive end-expiratory pressure (PEEP) on functional residual capacity (FRC) formation at birth were investigated. Preterm rabbit pups (28 d) were randomized at birth into four groups (n = 6 for each): 1) SI, PEEP 5 cm H2O, 2) no SI, PEEP 5 cm H2O, 3) no SI + no PEEP, 4) SI + no PEEP. FRC and tidal volume (Vt) were measured by plethysmography and uniformity of lung aeration by phase contrast x-ray imaging. Ventilation with a SI and PEEP uniformly aerated the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
147
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 36 publications
7
147
0
4
Order By: Relevance
“…A SI focuses on the initial fluid clearance and aeration but its value depends on subsequent respiratory management maintaining aeration. PEEP is essential in the preterm lung (5,14). In our study, we used a PEEP (8 cmH 2 O) previously shown to be appropriate in preterm lambs (6,11,16,17), and higher than that used in similar animal studies (5,9,10,14,15,20,29), suggesting our results are due to differences in recruitment strategy and not subsequent ventilator management.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…A SI focuses on the initial fluid clearance and aeration but its value depends on subsequent respiratory management maintaining aeration. PEEP is essential in the preterm lung (5,14). In our study, we used a PEEP (8 cmH 2 O) previously shown to be appropriate in preterm lambs (6,11,16,17), and higher than that used in similar animal studies (5,9,10,14,15,20,29), suggesting our results are due to differences in recruitment strategy and not subsequent ventilator management.…”
Section: Discussionmentioning
confidence: 87%
“…To achieve lung aeration at birth, and then maintain recruitment and tidal ventilation, a recruitment strategy needs to overcome specific the mechanical and time constant constraints of the respiratory system (1,6,23). Practically, this requires an adequate inflating pressure and/or PEEP to be applied for a sufficient duration to achieve volume change (5,9,23). The preterm lamb is known to require a longer and higher inflating pressure to achieve lung aeration (10,13,20,23) than has been advocated in human trials (19,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This creates a pressure gradient that facilitates the movement of liquid across the distal airways into the surrounding tissue (19), from where it is cleared (13,20). Because hydrostatic pressure gradients facilitate lung aeration, we investigated the effect of PEEP and sustained inflations on lung aeration at birth in preterm rabbits (9,21,22) using synchrotron-based imaging techniques (23). These studies demonstrated that both pressure and the time over which the pressure is applied (pressure-time integral) are important for facilitating and maintaining FRC immediately after birth.…”
mentioning
confidence: 99%